An Assessment of Operation and Maintenance of Trail Bridges for Sustainable Mobility in Nepal - Budha, Prem Bahadur; Joshi, Buddhi Raj (Himalayan Journal of Applied Science and Engineering, 2022)
Trial bridges have a significant impact on mobility and socioeconomic status in rural regions of Nepal. The construction of the trail bridges is the important transportation mobility of Nepal to enhance rural mobility. It is essential to establish an effective operation and maintenance (O&M) plan for the long-term sustainability of the trail bridges. Proper O&M mechanism has a significant impact on safe, secure, durable, and sustainable service in the community. In our context, it is very challenging due to a lack of proper technology, a proper management system, and a scarcity of resources. The study was focused on evaluating the implementation status of operation and maintenance of trail bridges in Mugum Karmarong Rural Municipality of Mugu district of Nepal. Quantitative and qualitative data have been collected to evaluate the operation and maintenance status of twenty bridges. The related officials, businessmen, teachers, students, local community members, user group members, health workers, and other stakeholders of Trail Bridge were considered for the survey. The design guidelines, published literature, and other related guidelines of the Government of Nepal (GoN) were analyzed for the research. The convenient survey was conducted from sampled respondents along with three focus group discussions in three trail bridge projects. Further, key informants were interviewed comprising different stakeholders involved in the project planning and implementation process from central to the local level. The quantitative and quantitative data has been adopted and analyzed using a simple statistical method has performed for quantitative data analysis, and the content analysis method is used to interpret qualitative findings. The study concluded that the overall implementation status of O&M of trail bridges in Mugum Karmarong Municipality is disappointing and needs immediate operation and maintenance. The study indicates that proper O&M of trail bridges have a significant reduction in time to reach the school and health service is directly related to increased enrollment in schools and increased health facilities in communities, respectively. The income status and livelihood of people in communities have improved due to an increase in mobility and market accessibility from the operation of trail bridges . The output of this study will be the milestone for the proper operation, and management system development for sustainable, reliable, and cost-effective infrastructure development in the country.